Electrical wiring commercial - Mullin, Ray C. (Delmar Thomson Learning, 2002)
. Used by thousands of apprentices to prepare for and successfully pass journeyman exams, this edition has been thoroughly updated based on current 2002 NEC requirements. Metrification and adoption of the new Code numbering system is just the beginning! This edition has also been significantly expanded and now features an introduction to cube fuse, plus all-new information on IC luminaries as well as Transient Voltage Surge Suppressor and Uninterruptible Power Supply. Comprehensive in scope, the book enables readers to gain expertise in identifying, interpreting, and applying applicable Code rules as they proceed, room by room, through the wiring of an insurance office, doctor's office, bakery, beauty salon, and basement with an electric boiler. Hundreds of examples, sample calculations, wiring diagrams, illustrations and photos are included to guide them, step-by-step, through wiring sizing, load calculations, conduit fill computations, selecting overcurrent protection, and more!